Enhanced Cd extraction of oilseed rape (Brassica napus) by plant growth-promoting bacteria isolated from Cd hyperaccumulator Sedum alfredii Hance. Issue 3 (4th March 2017) - Pan, Fengshan; Meng, Qian; Luo, Sha; Shen, Jing; Chen, Bao; Khan, Kiran Yasmin; Japenga, Jan; Ma, Xiaoxiao; Yang, Xiaoe; Feng, Ying
ABSTRACT: Four plant growth-promoting bacteria (PGPB) were used as study materials, among them two heavy metal-tolerant rhizosphere strains SrN1 ( Arthrobacter sp.) and SrN9 ( Bacillus altitudinis ) were isolated from rhizosphere soil, while two endophytic strains SaN1 ( Bacillus megaterium ) and SaMR12 ( Sphingomonas ) were identified from roots of the cadmium (Cd)/zinc (Zn) hyperaccumulator Sedum alfredii Hance. A pot experiment was carried out to investigate the effects of these PGPB on plant growth and Cd accumulation of oilseed rape ( Brassica napus ) plants grown on aged Cd-spiked soil. The results showed that the four PGPB significantly boosted oilseed rape shoot biomass production, improved soil and plant analyzer development (SPAD) value, enhanced Cd uptake of plant and Cd translocation to the leaves. By fluorescent in situ hybridization (FISH) and green fluorescent protein (GFP), we demonstrated the studied S. alfredii endophytic bacterium SaMR12 were able to colonize successfully in the B. napus roots. However, all four PGPB could increase seed Cd accumulation. Due to its potential to enhance Cd uptake by the plant and to restrict Cd accumulation in the seeds, SaMR12 was selected as the most promising microbial partner of B. napus when setting up a plant–microbe fortified remediation system.